Efficacy and Safety of Probiotic Use in Preterm Infants Remains Unproven. Issue 6 (November 2021) - Beal, Judy A.
Abstract : Probiotics are commonly used for preterm infants in the neonatal intensive care unit. Our pediatric nursing expert, Dr. Beal, explains the current evidence and recent advisory on probiotics for preterm infants by the American Academy of Pediatrics.